2022
DOI: 10.1186/s12913-022-08239-0
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for acute cardiovascular diseases: a scoping review

Abstract: Background Although many quality indicator (QI) sets have been developed for acute cardiovascular diseases, a comprehensive summary is lacking. In this scoping review we aimed to summarize the available evidence on the QI sets for acute cardiovascular diseases, and assess the QI set development process. We followed the Joanna Briggs Institute framework and the PRISMA extension for scoping reviews. Methods We conducted a systematic search of MEDLINE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The use of QI has garnered the interest of multiple stakeholders, including academic societies, payers, and the public. 2 , 8 , 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of QI has garnered the interest of multiple stakeholders, including academic societies, payers, and the public. 2 , 8 , 9 …”
mentioning
confidence: 99%
“…Various QIs have been used in the context of PCI, including door-to-balloon (D2B) time in ST-segment elevation myocardial infarction (STEMI) and the implementation of transradial intervention (TRI). 9 , 10 Although adherence to such QIs in these settings has been linked to improved outcomes according to various benchmarking methods, 3 , 11 , 12 , 13 , 14 the optimal approach for providing feedback to enhance compliance with QIs remains uncertain. 15 , 16 These interventions may be one time, regular, real time, interactive, or multifaceted (eg, checklists and educational materials).…”
mentioning
confidence: 99%
“…Reviewing these two medical conditions provided an in-depth understanding of quality measures that should be monitored in a wide range of medical conditions (Kanaoka et al, 2022;Aktaa et al, 2022;Rajaguru et al, 2022). The evidence included in Chapter 2 revealed that measures of survival and disease control are commonly used in VBHC.…”
mentioning
confidence: 99%